PP.20.17: MEDICAL THERAPY PRESCRIPTION AT DISCHARGE AFTER TYPE A AORTIC DISSECTION CURE. (June 2015) - Delsart, P.; Boudghene-Stambouli, F.; Vincentelli, A.; Juthier, F.; Jegou, B.; Koussa, M.; Fayad, G.; Modine, T.; Haulon, S.; Mounier-Vehier, C.
Abstract : Objective: The association between a structural anomaly of the aortic wall and uncontrolled hypertension are the main causing factors of aortic dissection. Follow-up management is based on an optimal blood pressure control. The data on blood pressure control and on medical therapy prescription at discharge after an acute surgery in this population are scares. Design and method: We retrospectively analyzed the data of 74 patients hospitalized from 2005 to 2010 for an emergency surgical type A aortic dissection. All patients benefited of a 24-hour blood pressure monitoring at discharge, medical prescription before admission and at discharge were collected. Statistical analyses were made with non parametric tests. Results: 67% of the population was male, median age of 53 years, 9.5 % with a prior history of ascending aorta aneurysm, 6.7 % with an elastic aortic wall disease. 50% take an antihypertensive therapy before admission, 8% of patients received 3 or more drugs, 4 % of diabetes mellitus, 31 % of former smoker and median Body Mass Index was of 26.4 Kg/m 2 . We note 23 % of left ventricular hypertrophy on electrocardiogram. The median systolic and diastolic blood pressure on the 24 h monitoring were respectively 125/71 mmHg. The results on medical therapy prescription are summarized in the Table. Figure. No caption available. Conclusions: The prescription of medical therapy before hospital discharge is not optimal. A closed collaboration between cardiologists and surgeons should be proposed. The prevalence of a non dipping status on blood pressure monitoring is very high, a systematic screening of sleep apnea syndrome should be discussed in this context.